Sino-Western Interaction and A Preliminary Deconstruction of the Tianxia Concept from 1600 to 1840 - Zhang, Jinghong (Thai Journal of East Asian Studies, 2023)
Sino-Western interaction began around 1600, mainly in terms of Western learning spreading to the East. Western missionaries led by Matteo Ricci imported Western artifacts into China. At the time, China offered creative feedback under the influence of Western learning. Tianxia is a historical Chinese cultural concept that denoted either the entire geographical world or the metaphysical realm of mortals, and later became associated with political sovereignty. A preliminary deconstruction of the Tianxia concept is evident in the feedback process. This paper uses David Easton’s input-output analysis to explain preliminary deconstruction of Tianxia conceptualizing in four sections: 1) Tianxia internal logic as political system; 2) preliminary deconstruction of the Tianxia concept at the height of Sino-Western interaction; 3) preliminary deconstruction of Tianxia during a lull in Sino-Western exchange; and 4) The Tianxia concept in other East Asian cultural and political entities. Results were that preliminary deconstruction of Tianxia did not amount to complete disintegration, but included supplementing the original concept and changing its qualities by evolving into a new concept through quantitative change.